The Analysis of Physiological Variations in M2 Generation of Solanum melongena L. Mutagenized by Ethyl Methane Sulfonate - Xi-ou, Xiao; Wenqiu, Lin; Wei, Li; Xiaoming, Gao; Lingling, Lv; Feiyue, Ma; Yuge, Liu (Frontiers in Plant Science, 2017)
The eggplant was mutagenized with ethyl methane sulfonate (EMS) to enhance its genetic variability in our previous paper. In this article, we further analyzed the phenotype of M2 generation of mutant eggplants. A total of 325 independent M2 families were investigated for phenotypic variation. In addition to the visible phenotypic variation, chlorogenic acid concentrations were analyzed in 26 fruits of mutants with HLPC assay. 17 fruits exhibited significantly higher concentrations of chlorogenic acids than those in wild-type. The anthocyanin concentration of S9-1, the purple black mutant, was higher than WT, meanwhile, the anthocyanin concentration of L6-4 and U36-1 was lower than WT. Furthermore, our RT-PCR result demonstrated that the expression levels of anthocyanin biosynthetic genes, except for SmPAL, were increased in S9-1, and the regulator SmMYB1 was decreased in L6-4 and U36-1 mutants. Together, our data indicated that, M2 generation showed abundant phenotypic variations and the strong potential usage for next step of breeding and molecular genetic mechanisms in eggplant.